(untitled) (Research, Society and Development, 2021)
Demands for dental treatments for gingival recessions are increasing every day, the aesthetic compromise and hypersensitivity caused by this change in the periodontium is something that causes a lot of discomfort in the population in general. Although there is a greater frequency in adults, some studies have shown that it occurs in children. The objective of this work was to carry out a narrative and current review of the last 10 years about the factors that may contribute to gingival recession in children. Different searches were performed in the Pubmed/Medline database. Eligibility criteria were: studies published in English, gingival recession, mucogingival disease, etiology, prevalence in children, cohort study, longitudinal and clinical cases. Exclusion criteria were age (cases over 19 years old), literature review, texts outside the topic. Of the total texts found, only 9 met the inclusion criteria. We conclude that, in the last 10 years, there has been no research on the topic of primary dentition. The manifestations described here as: bruxism, orthodontic treatment, systemic diseases, malocclusions, labial frenulum were related in children, however, in mixed and/or permanent dentition phase.